Genetic variation in an ephemeral mudflat species: The role of the soil seed bank and dispersal in river and secondary anthropogenic habitats. Issue 8 (17th March 2020) - Böckelmann, Jörg; Tremetsberger, Karin; Šumberová, Kateřina; Kohl, Gudrun; Grausgruber, Heinrich; Bernhardt, Karl‐Georg
Abstract: Many ephemeral mudflat species, which rely on a soil seed bank to build up the next generation, are endangered in their natural habitat due to the widespread regulation of rivers. The aim of the present study was to elucidate the role of the soil seed bank and dispersal for the maintenance of genetic diversity in populations of near‐natural river habitats and anthropogenic habitats created by traditional fish farming practices using Cyperus fuscus as a model. Using microsatellite markers, we found no difference in genetic diversity levels between soil seed bank and above‐ground population and only moderate differentiation between the two fractions. One possible interpretation is the difference in short‐term selection during germination under specific conditions (glasshouse versus field) resulting in an ecological filtering of genotypes out of the reservoir in the soil. River populations harbored significantly more genetic diversity than populations from the anthropogenic pond types. We suggest that altered levels and patterns of dispersal together with stronger selection pressures and historical bottlenecks in anthropogenic habitats are responsible for the observed reduction in genetic diversity. Dispersal is also supposed to largely prohibit genetic structure across Europe, although there is a gradient in private allelic richness from southern Europe (high values) to northern, especially north‐western, Europe (low values), which probably relates to postglacial expansion out of southern and/or eastern refugia. Abstract : Using microsatellite markers, we found no difference in genetic diversity levels between soil seed bank and above‐ground population and only moderate differentiation between the two fractions in the mudflat species Cyperus fuscus, possibly as a result of differences in short‐term selection during germination under specific conditions (glasshouse versus field) resulting in an ecological filtering of genotypes out of the reservoir in the soil. River populations, however, harboured significantly more genetic diversity than populations from fishponds and fish storage ponds, supposedly because of differences in the strength of selection pressures, historical bottlenecks, and altered levels and patterns of dispersal.